Determinants of Fertility Change in the Period 2006-2011 among Women Aged 15-49 Years in Uganda - Ariho, Paulino; Kabagenyi, Allen; Nzabona, Abel (PAA 2018 Annual Meeting, 2018)
Studies on fertility in Uganda have highlighted the importance of demographic and socioeconomic factors in fertility change but have not isolated the portion of fertility change attributable to changing characteristics of women from that due to changing behavioral effects. Methods: Using DHS survey data for Uganda, we decomposed the 2006-2011 change in fertility among women aged 15-49 years into portions attributable to changing characteristics of women and changing behavioral effects. Results: The overall change in fertility was largely attributed to changing characteristics of women aged 15-49 years in the 2006-2011 period rather than changing behavioral effects. Change in education level attained and age at first marriage contributed the biggest percentage to change in fertility between 2006 and 2011. Other significant contributors were changes in; family size preference, women’s working status, contraceptive use, exposure to family planning messages, place of residence and age at first sex. Conclusion: This paper suggests that improvements in social, economic and demographic characteristics of Ugandan women are the key drivers of the reduction in fertility levels in Uganda. With continued improvement in secondary school completion, age at first marriage, contraceptive use and family size preferences will continue to be an important factor of Uganda’s fertility transition. It is imperative for government and other stakeholder to work out appropriate strategies to ensure that girls complete at least secondary level of education
Keywords: Change in fertility; Children ever-born; Decomposition; Socioeconomic factors; Demographic factors; Changing characteristics; Changing effects; Uganda